How to write a Critically Appraised Topic: evidence to underpin routine clinical practice. (1st October 2017) - Callander, J.; Anstey, A.V.; Ingram, J.R.; Limpens, J.; Flohr, C.; Spuls, P.I.
Summary: Critically appraised topics (CATs) are essential tools for busy clinicians who wish to ensure that their daily clinical practice is underpinned by evidence‐based medicine. CATs are short summaries of the most up‐to‐date, high‐quality available evidence that is found using thorough structured methods. They can be used to answer specific, patient‐orientated questions that arise recurrently in real‐life practice. This article provides readers with a detailed guide to performing their own CATs. It is split into four main sections reflecting the four main steps involved in performing a CAT: formulation of a focused question, a search for the most relevant and highest‐quality evidence, critical appraisal of the evidence and application of the results back to the patient scenario. As well as helping to improve patient care on an individual basis by answering specific clinical questions that arise, CATs can help spread and share knowledge with colleagues on an international level through publication in the evidence‐based dermatology section of the British Journal of Dermatology .